Metals in the surface sediments of Istanbul Strait (Turkey) - (:unkn) unknown (TAYLOR & FRANCIS INC, 2008)
Surface sediments from 17 stations in the Istanbul Strait and Marmara Sea were collected and analysed for major and trace elements by wavelength-dispersive X-ray fluorescence spectrometry (WDXRF). Metal concentrations in surface sediments varied from 1.3 to 7.2 % for Al, 4.8 to 18 mg kg- 1 for As, 119 to 599 mg kg- 1 for Ba, below detection limit (bdl) to 6.6 mg kg- 1 for Cd, 18 to 222 mg kg- 1 for Cr, 7.6 to 180 mg kg- 1 for Cu, 1.0 to 5.5 % for Fe (10 000 to 55 000 mg kg- 1), 171 to 718 mg kg- 1for Mn, 3.3 to 64 mg kg- 1 for Ni, 4.5 to 461 mg kg- 1 for Pb, 1.3 to 68 mg kg- 1 for Sn, 19 to 170 mg kg- 1 for V and 16 to 859 mg kg- 1 for Zn. Three tools have been applied in order to evaluate metal pollution in the sediments; Sediment quality guidelines (SQGs), enrichment factors (EFs) and geoaccumulation index (Igeo). SQGs values indicate that Pb and Ni are the most likely contaminants to cause adverse biological effects. On the other hand, both metal enrichment factors and geoaccumulation index show that As, Zn, Pb and Cd contaminations exist in the entire study area and contamination of other metals is also present in some sites depending on the sources. Factor analysis (FA) receptor modelling technique was applied to investigate the sources affecting surface sediment samples at the Istanbul Strait.
Keywords: Metals; sediment; SQGs; enrichment factor; geoaccumulation index; factor analysis; TRACE-METALS; MULTIVARIATE-ANALYSIS; HEAVY-METALS; HONG-KONG; RECEPTOR MODELS; BOSPORUS STRAIT; CONTAMINATION; ELEMENTS; WATER; POLLUTION